Guerillas in the midst a narrative on the rise of Mindanao cinema in the digital age - Cañedo, Dax (2017)
Access online through this link: https://www.plarideljournal.org/article/guerillas-midst-narrative-rise-mindanao-cinema-digital-age
Keywords: Filmmaking; Motion picture industry; Motion pictures -- Mindanao